PENGARUH KECENDERUNGAN MANAJER DALAM PEMBUATAN KEPUTUSAN TERHADAP PAYOFF MAGNITUDE - David Prasetya; Baldric Siregar (Jurnal Riset Akuntansi dan Keuangan, 2012)
The objective of this research is to obtain empirical evidence regarding the factors that influence managers propensity to take risk which the effects of payoff magnitude (the magnitudeof the project selection). Propensity to take risk consists of risk taking managers and risk taking managers. Experiment is designed by using factorial design 1 x 3 between subjects. Fifty-two students, consisted of STIE YKPN Yogyakarta’s students from Master of Accounting program, Master of Management program, and PPA program, are participate in this experiment.Subjects are selected as the proxy of manager because of the difficulties to obtain actual manager, by consideration that most of students from Master of Accounting program, Masterof Management Program, and PPA program are candidate manager. In general, the results show that propensity to take risk effect on payoff magnitude. Of the six factors studied, onlyfour are shown to influence propensity to take risk. Those factors are probability that generate a loss, probability that no bonus, maximum bonus available, and weigthed average expectedbonus. The results show that gender do not influence propensity to take risk.Keywords: propensity to take risk, risk averse, risk taking, payoff magnitude, and gender